Fruit and vegetable consumption and mortality: european prospective investigation into cancer and nutrition - Leenders, Max; Sluijs, Ivonne; Ros, Martine M.; Boshuizen, Hendriek C.; Siersema, Peter D.; Ferrari, Pietro; Weikert, Cornelia; Tjønneland, Anne; Olsen, Anja; Boutron-Ruault, Marie-Christine; Clavel-Chapelon, Françoise; Nailler, Laura; et al. (American journal of epidemiology, 2013)
In this study, the relation between fruit and vegetable consumption and mortality was investigated within the European Prospective Investigation Into Cancer and Nutrition. Survival analyses were performed, including 451,151 participants from 10 European countries, recruited between 1992 and 2000 and followed until 2010. Hazard ratios, rate advancement periods, and preventable proportions to respectively compare risk of death between quartiles of consumption, to estimate the period by which the risk of death was postponed among high consumers, and to estimate proportions of deaths that could be prevented if all participants would shift their consumption 1 quartile upward. Consumption of fruits and vegetables was inversely associated with all-cause mortality (for the highest quartile, hazard ratio = 0.90, 95% confidence interval (CI): 0.86, 0.94), with a rate advancement period of 1.12 years (95% CI: 0.70, 1.54), and with a preventable proportion of 2.95%. This association was driven mainly by cardiovascular disease mortality (for the highest quartile, hazard ratio = 0.85, 95% CI: 0.77, 0.93). Stronger inverse associations were observed for participants with high alcohol consumption or high body mass index and suggested in smokers. Inverse associations were stronger for raw than for cooked vegetable consumption. These results support the evidence that fruit and vegetable consumption is associated with a lower risk of death.
Gesehen am 04.11.2021